Witnessing terrorism. (September 2015) - Howie, Luke
Witnessing is never merely watching or seeing. Witnessing is never a passive practice. Witnessing is active, a performance, an embodied experience. Given the hypermediated nature of the contemporary social world witnessing is particularly common when practised large distances from events. Contemporary terrorists, and their counterparts waging the so-called global 'war on terror', depend on near and distant witnesses to spread their violent messages and influence target audiences. Witnessing, however, shows itself to be contradictory and unreliable just like the people who do it, all of whom endure disowned desires and fears. Drawing on the Smithsonian, the September 11 Digital Archive and the story of lower Manhattan graphic novelist Art Spiegelman, I argue that witnessing is what is most at stake in any attempt to understand the meanings and consequences of contemporary terrorism.